Measurement of some heavy metals concentration in live feed commonly used in aquaculture - Z. Hashemi Hosseinabadi; S. Soltanian; M. Akhlaghi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
The aim of the current investigation was to determine the concentration of some heavy metals in a number of aquatic invertebraes commnly used as live feed in aquaculture. For this goal, samples of blood worm, sludge worm, earthworm, gammarus, shelled snail, freshwater ghost shrimp and tiny marine shrimp were prepared from aquatic environment or from imported live feeds. Samples were digested chemically and the atomic absorption were recorded as µg/g dry weight. Results showed that the highest level of heavy metals concentration were detected in live feeds as follows: iron (213.4±10.2), cadmium (1.15±0.013) and nickel (20.97±3.6) in earthworm; zinc (105.71±5.8), chrome (19.63±5.3) in sludge worm; copper (37.34±4.2) in freshwater ghost shrimp and lead (24.71±4.7) in tiny marine shrimp respectively. It is proposed that high rates of heavy metals detected in some of live feeds in the present study may eventually have a severe negative impact on fish and human health conditions. Therefore, .....